Developing Teaching Materials Based on Constructivism Arabic Learning in KTSP Curriculum/ تطوير المواد الدراسية على أساس المدخل البنائي لتعليم اللغة العربية في ضوء المنهج الدراسي على مستوى الوحدة التربوية - Ana Achoita (Universitas Negeri Malang, 2021)
The aim of this research is to improve teaching materials based on constructivist Arabic learning and oriented KTSP for first-class students of SMP